Application of a 2D-Hydrodynamic Model to Assess the Impact of Spring Water Discharge into the Lake Pamvotida in Ioannina, Greece (Poster Presentation) - K. Zachopoulos; Papadimos, D. (2025)
Poster Presentation in 13th World Congress of EWRA on Water Resources and Environment, Palermo, Italy 24 - 28 2025